Anxiety-like behaviour is regulated independently from sex, mating status and the sex peptide receptor in Drosophila melanogaster. (August 2020) - Bath, Eleanor; Thomson, Jessica; Perry, Jennifer C.
Abstract : Sex differences in anxiety-related behaviours have been documented in many animals and are notable in human populations. A major goal in behaviour research is to understand why and how sex differences in cognitive-emotional states like anxiety arise and are regulated throughout life. Anxiety allows individuals to detect and respond to threats. Mating is a candidate regulator for anxiety because threats are likely to change, often in sex-specific ways, when individuals shift to a postmating reproductive state. However, we know little about how mating mediates anxiety-related behaviour in males and females, or about how males might influence female anxiety via seminal proteins transferred during mating. To address this gap, we examined anxiety-related behaviour in the fruit fly Drosophila melanogaster, an emerging model animal for anxiety, with respect to sex, mating and sex peptide, a seminal protein known to modulate a host of female postmating responses in fruit flies. We assayed anxiety-like behaviour using the open-field assay to assess individual avoidance of the interior of an arena ('wall-following' behaviour). We found sex differences in activity level, but no evidence for sex differences in wall-following behaviour. We found no effects of mating in either sex, or of the presence of the sex peptide receptor in females, on wall following. Our results suggest that anxiety is not one of the cognitive-emotional states regulated by mating and sex peptide in fruit flies, and that researchers need an alternative model for sex differences in anxiety. Highlights: Many animals display anxiety, but few studies have compared males and females. In fruit flies, we found no sex differences in anxiety-like behaviour. Mating could modulate anxiety, directly or via male ejaculate proteins. We found that anxiety was independent from mating and the sex peptide protein. Anxiety is not part of the postmating behavioural shift in fruit flies.